2015
DOI: 10.1002/2014gl062598
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for generation of unstable suprathermal electron population in the auroral F region

Abstract: Anomalous incoherent scatter radar (ISR) spectra confined to narrow altitude ranges near the F region peak and correlated with dynamic auroral precipitation have previously been identified and explained in terms of the cavitating beam-driven Langmuir turbulence. In this work we used a one-dimensional Zakharov simulation to constrain the range of physical mechanisms underlying these observational features. We find that although Langmuir wave collapse and caviton formation generated by electron beams with energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…ISR detections are much different from in situ measurements in that they indicate enhanced wave activities at a specific spatial scale, determined by the ISR probing wave number. This, in turn, puts additional requirements on the characteristic energy of the electron beams and/or the dynamics of turbulence (for more context see Akbari et al []).…”
Section: Introductionmentioning
confidence: 99%
“…ISR detections are much different from in situ measurements in that they indicate enhanced wave activities at a specific spatial scale, determined by the ISR probing wave number. This, in turn, puts additional requirements on the characteristic energy of the electron beams and/or the dynamics of turbulence (for more context see Akbari et al []).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, conjugate measurements by radars and high-resolution optical imagers have shown that LT echoes are associated with dynamic smallscale auroral structures likely related to dispersive-scale Alfvén waves (see Figures 9A,B). Results from one-dimensional Zakharov simulations suggest that the measured ISR spectra are best reproduced numerically when the modeled electron beams extend a positive slope to energies as low as 5 eV, such that ion-acoustic waves are induced by parametric decays at wavenumbers greater than k detection (Akbari et al, 2015). Such low energy components of an electron beam, however, would likely be significantly modified by collisions at altitudes of some radar observations between 180 and 300 km.…”
Section: Discussion Of Several Open Questionsmentioning
confidence: 97%
“…Such low energy components of an electron beam, however, would likely be significantly modified by collisions at altitudes of some radar observations between 180 and 300 km. This leads to a speculation that perhaps an unstable feature of the electron distribution function which eventually gives rise to LT echoes is produced locally at ionospheric heights in response to electron precipitation (Akbari et al, 2015). Such a speculation, however, is not backed with concrete evidence.…”
Section: Discussion Of Several Open Questionsmentioning
confidence: 98%
“…The SimISR tool is useful for identifying situations where assumptions in the parameter fitting break down. For example, a number of studies have explored the case where ISR parameter measurements and spectra show evidence of non‐Maxwellian plasma behavior [see, e.g., Akbari et al , , , for AMISR examples]. Future studies using the simulator could help create a training set that can be used with a pattern recognition algorithm to identify cases where normal fitting procedures may be incorrect due to violation of Maxwellian assumptions.…”
Section: Simulation Examplesmentioning
confidence: 99%